High-resolution absorption measurements of NH3 at high temperatures: 500–2100 cm−1. (December 2015) - Barton, Emma J.; Yurchenko, Sergei N.; Tennyson, Jonathan; Clausen, Sønnik; Fateev, Alexander
Abstract: High-resolution absorption spectra of NH3 in the region 500–2100 cm −1 at temperatures up to 1027 °C and approximately atmospheric pressure (1013±20 mbar) are measured. NH3 concentrations of 1000 ppm, 0.5% and 1% in volume fraction were used in the measurements. Spectra are recorded in high temperature gas flow cells using a Fourier Transform Infrared (FTIR) spectrometer at a nominal resolution of 0.09 cm −1 . Measurements at 22.7 °C are compared to high-resolution cross sections available from the Pacific Northwest National Laboratory (PNNL). The higher temperature spectra are analysed by comparison to a variational line list, BYTe, and experimental energy levels determined using the MARVEL procedure. Approximately 2000 lines have been assigned, of which 851 are newly assigned to mainly hot bands involving vibrational states as high as v 2 =5. Abstract : Highlights: Absorption spectrum of ammonia recorded at 1300 K. 2000 line assignments, 851 newly assigned. Several bands observed for the first time.